2015
DOI: 10.1016/j.procir.2015.06.072
|View full text |Cite
|
Sign up to set email alerts
|

Sensor Monitoring during Tack Welding of Aerospace Components

Abstract: In the 21 st century, a growing attention is being paid to the implementation of sensor monitoring systems for innovative production environments based on the conviction that monitoring and control of manufacturing processes is an essential issue to fabricate products with very high quality. In an effort towards zero defect manufacturing concept implementation, an on-line sensor system was developed by incorporating modern technologies of 2D laser distance measurements for process monitoring and control during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…A growing attention is being paid to the implementation of sensor monitoring systems for innovative production environments based on the conviction that monitoring and control of manufacturing processes is an essential issue to fabricate products with very high quality (Centobelli et al , 2015). In the article Yang et al (2013), a type of pit supporting structure, which was tested and verified using the sensor monitoring technology, was presented, and the monitoring data of the field tests were shown that the new supporting structure was convenient, reliable and safe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing attention is being paid to the implementation of sensor monitoring systems for innovative production environments based on the conviction that monitoring and control of manufacturing processes is an essential issue to fabricate products with very high quality (Centobelli et al , 2015). In the article Yang et al (2013), a type of pit supporting structure, which was tested and verified using the sensor monitoring technology, was presented, and the monitoring data of the field tests were shown that the new supporting structure was convenient, reliable and safe.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration monitoring is a method of technical diagnostics which could be used for monitoring of a technical state of a device by observing the level of a mechanical oscillation in a real time (Milovančević et al , 2017, 2015, 2010). Systems failures could be detected by the vibration diagnostics (Centobelli et al , 2015; Yang et al , 2013). Planetary power transmission in pellet mills was investigated in this article to predict the vibration state.…”
Section: Introductionmentioning
confidence: 99%